Chronic venous insufficiency in the elderly - Castillo De La Cadena, Luis A. (2022)
Chronic venous insufficiency (CVI) is a frequent vascular pathology in the elderly and generates difficulties in its diagnosis and treatment due to the presence of comorbidities. A narrative review was carried out from the search in five databases: PubMed, Scielo, Lilacs, Clinical Key (Elsevier) and Ebsco. In the geriatric population, more severe stages of the disease occur, such as edema and trophic changes in the leg, due to the pre-existence of chronic venous disease. The main risk factors for disease progression are obesity, limited mobility and comorbidities. Diagnosis is based on clinical suspicion and confirmation with venous echo Doppler of the lower limbs. Systemic causes of lower limb edema such as heart failure, renal or hepatic dysfunction, and the use of hypertensive medications should be considered in the differential diagnosis. Other differential diagnoses are lymphedema, subclinical venous thrombosis, and chronic lower limb pain. Treatment includes patient education, compression stockings, medical and surgical treatment. In conclusion, chronic venous insufficiency is a frequent and more severe disease in elderly patients. Obesity, poor mobility and comorbidities are the risk factors associated with the progression of the disease. Patient education, use of compression stockings, and phlebotonics are effective in treatment. Surgical / endovenous treatment has good effectiveness in elderly patients suffering from CVI.